(untitled) (Research, Society and Development, 2021)
Antimicrobials are drugs capable of containing and reducing the proliferation of pathogenic microorganisms, among which we can highlight bacteria, fungi.Its prescription is indispensable in dental practice and, therefore, it is necessary to know about its oral repercussions, dosage and contraindications. This work aims to make a critical review of the most recent literature on the most used antimicrobials in dental practice. For this purpose, the descriptors were cross-referenced in databases in the period between 2010 and 2020 and among bacterial infections, the following stand out: pulpitis, odontogenic abscesses, periodontal and periapical changes and bacterial endocarditis.While in fungal infections, the most common is candidiasis, which is usually treated by two classes of antifungals: polyenic and azoles.